Relationships between M.B. A. Program Attributes and Personal Characteristics of Students - Ahmed, Sadrudin A (Canadian Journal of Higher Education, 1981)
This paper investigates the relationship between the personal characteristics of newly enrolled M.B. A. students and the importance these students place on various M.B.A. pro- gram attributes. Survey data from 165 students entering three Canadian M.B.A. programs indicates that the program attributes which had the strongest relationship with the per- sonal characteristics of the students were the use of the case method of teaching and social life/recreation. The personal characteristics which showed the strongest relationship with the attribute importance were age and the mother tongue of the students.